Response in a child with a BRAF V600E mutated desmoplastic infantile astrocytoma upon retreatment with vemurafenib - Tilburg, Cornelis M. van; Selt, Florian; Sahm, Felix; Bächli, Heidi; Pfister, Stefan; Witt, Olaf; Milde, Till (Pediatric blood & cancer, 2018)
Infants with low-grade glioma (LGG) and diencephalic syndrome have a poor outcome. The patient described here had a desmoplastic infantile astrocytoma harboring a BRAF V600E mutation. After relapse following initial standard chemotherapy treatment, he was successfully treated with the BRAF V600E inhibitor vemurafenib at the age of 3 years 11 months and 5 years 0 months. A rapid response was observed on both occasions. This illustrates the possibility of continuous oncogenic addiction and the therapeutic potential of BRAF V600E inhibitor monotherapy in LGG, even in very young severely compromised children. BRAF V600E inhibition in LGG and possible (re-)treatment regimens are briefly discussed.